Shortening Activated Partial Tromboplastin Time (APTT) Between Hypertension and Nonhypertension in Diabetic Mellitus Patients with Bevacizumab Intravitreal Injection - Anik Ika Winarni; Ni Luh Putu Widyasti; Natalia Christina Angsana; Rizto Wisuda Senuari; Angela Nurini Agni; Agus Supartoto; Muhammad Bayu Sasongko; Haryo Yudono (Indonesian Vitreoretinal Society, 2019)
Introduction : Bevacizumab intravitreal injection could be detectable in plasma that might interfere the coagulopathy and hemostasis condition. The purpose of this study was to investigate the difference of APTT between hypertensive and nonhypertensive diabetic mellitus patients with bevacizumab intravitreal injection. Methods : This was cohort study conducted at Sardjito General Hospital from March 2019 to June 2019. Thirty-two hypertension patients and 30 nonhypertension patients with diabetes mellitus who underwent bevacizumab intravitreal injection were included. Value of APTT was measured using ACLTOP300 machine prior and 1 week after IVB. The difference in mean APTT value prior and after IVB, range APTT value between two groups were assessed using independent t-test. The percentage of patients who had shortening of APTT in both groups was tested by two populations proportion test. Results : Mean APTT before IVB in hypertensive patients was 36.47 ± 2.92 seconds and in nonhypertensive patients was 36.33 ± 4.39 seconds with p value > 0.05. Mean value of APTT after IVB in hypertension patients was 35.42 ± 3.63 seconds and in nonhypertensive patients was 35.60 ± 3.13 seconds with p value > 0.05. APTT shortening in hypertensive patients was -1.03 ± 3.65 and nonhypertensive patients was -0.73 ± 2.55 with p value > 0.05. The risk of APTT shortening in hypertensive patients was 1.370 (0.831-2.258). The risk of APTT shortening in hypertensive patients who used antihypertensive drugs regularly was 0.538 (0.331- 0.874). Conclusion : There was no difference in shortening of APTT value 1 week after intravitreal bevacizumab injection between hypertensive and nonhypertensive groups in patients with diabetes mellitus. Hence, administration of IVB in hypertensive patients with regular antihypertensive therapy might be safe.